Effect of the supplemented media on the proliferated and differentiated capacities of in vitro cultured mouse stem cells - Thao, Do Thi; Hieu, Do Khac; Hung, Nguyen Mong (Academia Journal of Biology, 2014)
The ability of continuous dividing and differentiating into various cell types of living organisms is the potentials of stem cells which make them different from other normal cells. These potentials of stem cells arise many possible applications such as in practical treatment of diabetes, alzheimer, blood cancer, heart disease…, in the studies on carcinogenic process for future suggesting therapies, in producing transgenic animals for making valuable products, in genetic study and evolutional development. In our studies, we focused on the effects of supplement factors added into the growth media in order to regulate the proliferation and the specialization of stem cells. Our results showed that: 1. Mouse embryonic stem cells (ESC) were died when growing in the plain RPMI1640 medium (without FBS and without Feeder cells FC) due to the unsuitable medium. 2. Both the fetal bovine serum (FBS) and the newborn bovine serum (NBS) had effects on the stimulation of proliferation and differentitation of the ESC; however, FBS showed stronger effect than NBS. 3. The FC (after treatment with MC) as well as the 2 days FC growing extracted medium showed the same effect on the suppression of the differentiation but not the proliferation of the ESC. 4. The M5, M6 and M7 media were all able to be used for the culture of the mouse ESC. The choosen medium only was dependent on the laboratory availability and the scientific purposes.